Efeito do nitrogênio e do cobre na formação da martensita em aços inoxidáveis austeníticos e sua influência sobre o fenômeno de delayed cracking - Marta Ribeiro dos Santos (2008)
The influence of strain induced martensite, the residual stresses in redrawn cup edges and the degree of cold work on the susceptibility to Delayed Cracking Phenomenon of austenitic stainless steels were investigated. Four heats of austenitic stainless steels were used. It was observed that three of them exhibited the phenomenon in different drawing ratios in a period that begin and end within a 24h after redrawing process. These drawing ratios were determined as the Limited Drawing Ratio of the Delayed Cracking (LDR-DC). Additions of copper and nitrogen to austenitic stainless steels were effective in reducingthe susceptibility of Delayed Cracking Phenomenon and led to larger LDR-DC. In addition, copper and nitrogen stabilized the austenite in regard to martensitic transformation. The investigation of crack surfaces from the cups in which the Delayed Cracking has occurred revealed a brittle fracture character with transcrystalline and intergranular modes and sometimes, cleavage fractures features. In some fracture surface,both types of fracture existed side by side, and one finded transcrytalline fracture interspersed with intergranular constituents. During crack progression, crack colonies developed and linked together in a step-wise fashion, without branching, and propagated into the martensite packs. The residual stresses (mechanical factor) in the cups after forming and the high amount of strain induced martensite formed due to the degree of cold work associated to deep drawing and redrawing operations (metallurgical variables) were responsible for the occurrence of Delayed Cracking Phenomenon.